2018
DOI: 10.1021/jacs.8b01421
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Short Intermolecular Contacts Screens for Kinetic Stability in Packing Polymorphs

Abstract: Polymorphism is pervasive in molecular solids. While computational predictions of the molecular polymorphic landscape have improved significantly, identifying which polymorphs are preferentially accessed and experimentally stable remains a challenge. We report a framework that correlates short intermolecular contacts with polymorphic stability. The presence of short contacts between neighboring molecules prevents structural rearrangement and stabilizes the packing arrangement, even when the stabilized polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
1
27
2
Order By: Relevance
“…Short-contacts exist in neighboring molecules if the measured distance between two neighboring atoms is smaller than the sum of the van der Waals radii of the atoms. 45 We note that we adopted a definition of short-contacts (given directly by Mercury 3.9) that is slightly different from the recent report by Purdum, Loo, and colleagues, 46 in that we explicitly considered hydrogen−hydrogen interactions in our analysis. The α form of diTMS contains two short-contact interactions: one intralayer and another interlayer ( Figure 3a).…”
Section: Two Transition Pathways Of Nucleation and Growth Versus Coopmentioning
confidence: 99%
“…Short-contacts exist in neighboring molecules if the measured distance between two neighboring atoms is smaller than the sum of the van der Waals radii of the atoms. 45 We note that we adopted a definition of short-contacts (given directly by Mercury 3.9) that is slightly different from the recent report by Purdum, Loo, and colleagues, 46 in that we explicitly considered hydrogen−hydrogen interactions in our analysis. The α form of diTMS contains two short-contact interactions: one intralayer and another interlayer ( Figure 3a).…”
Section: Two Transition Pathways Of Nucleation and Growth Versus Coopmentioning
confidence: 99%
“…22 In a recent study it has been shown that in small p-conjugated molecules short intermolecular contacts stabilize the threedimensional packing arrangement and prevent structural rearrangement to the enthalpically favored stabilized polymorph. 39 With D-PDPP4T-HD as a start, 20 it is therefore of interest to explore the underlying structural characteristics that cause polymorphism in these polymers.…”
Section: Introductionmentioning
confidence: 99%
“…We attribute these changes to cold crystallization of the films, similar to processes observed in semicrystalline polymers that are quickly quenched below and subsequently heated above their glass transition temperatures. [ 58–66 ] In contrast, TBF thin films showed no evidence of morphological instability after aging as evidenced by the AFM images in Figure S5e,f, Supporting Information. A 2017 report from Hiszpanski et al.…”
Section: Resultsmentioning
confidence: 99%